PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK DENGAN MODERASI KEPEMILIKAN SAHAM OLEH KELUARGA - Shofia Nur Mumtahanah; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This study aims to know that the disclosure of Corporate Social Responsibility to tax aggressiveness with moderation of ownership of shares by the family.The population in this research is all mining sub-sector companies listed in BEI Period Year 2013 until Year 2015. The sample in this research is taken by using purposive sampling method. The analysis tool used is multiple linear regression analysis.Based on the results of the tests conducted it can be concluded that: CSR disclosure proved to affect the aggressiveness of corporate taxes, moderation of family ownership proved to increase the influence of CSR disclosure of tax aggressiveness by including control variables ROA, DER, firm size, capital intensity and R & D intensity, CSR disclosure of tax aggressiveness with moderation of family ownership may occur with the inclusion of controls of ROA, DER and firm size variables.